Nurse role: most significant changes between ATS (sanitary technician) and DUE (university diploma in nursing) - Nuria Martínez Cadaya; María Luz Fernández Fernández (Universidad de Alicante, 2012)
The health needs of the population have conditioned the professional role of nursing throughout history, and hence nursing functions have being redesigned, which is reflected in the professional practice. Presented below is a descriptive study carried out by a literature review that covers the period between 2000 - 2010, which objective is to identify the evolution of the nurse's role in Spain in the transition from "Sanitary Technical Assistant" qualification to Nursing degree. Through the analysis of the social, legal and formative context of the literature, it is evidenced the change in the nurse's role, changing its orientation towards the management of comprehensive care to the individual, expanding its roles to welfare, educational, management and researcher fields and using a scientific methodology based on the knowledge of their own discipline. However, these changes can be noticed more in the educational field than in the welfare field. It is concluded that the nurse's role has suffered significant changes since the implementation of the university studies although it does not achieve its real effectiveness. It is essential to deeply reflect on the reasons that prolong this situation and adopt the needed measures to fully assume the autonomous role.